Role of Racecadotril in Children with Acute Diarrhea - Sultana, Azmeri; Bishwas, Parijat; Islam, Shahidul; Ghosh, Uzzal Kumar; Iman, Kazi; Afroze, Sharmin; Sonia, Sheikh Farjana (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Diarrhea is a leading cause of illness and death among children in developing countries. Racecadotril (acetorphan), an enkephalinase inhibitor with antisecretory and anti-diarrheal actions, is an effective and safe treatment for acute diarrhea in adults and children. Objectives: The objective of this study is to evaluate the efficacy and tolerability of racecadotril as a treatment of acute diarrhea in children. Methods: This double-blind, randomized controlled clinical trial was conducted in Dr. MR Khan Children Hospital & Institute of Child Health over 1 year (June 2017- May 2018). The study was approved by the ethical committee of the institute. The efficacy and tolerability of racecadotril (1.5 mg/kg) administered orally 3 times daily) as adjuvant therapy to oral rehydration or intravenous fluid were compared with those of placebo in 40 children aged 3 months to 60 months of children who had acute diarrhea. Results: During the first 72 hours of treatment, patients receiving racecadotril had a significantly lower stool output (grams per hour) than those receiving placebo. The mean (±SE) 72-hours stool output was 54.75± 12.92 g per kilogram in the racecadotril group and 152.50±37.64 g per kilogram in the placebo group (p<0.001). The number of purging is significantly reduced in the racecadotril group than the placebo group (11.95±2.41 Vs 14.85±1.95, p= 0.000) on third day of admission. The duration of hospital stay is significantly lower in the racecadotril group than the placebo group (73.30±23.44 vs. 177.30±25.8. p= 0.000) group. Racecadotril was well tolerated; only 3 patients taking racecadotril had adverse effects like vomiting and 2 patients had hypokalaemia and 3 patients in the placebo group developed vomiting and 1patient developed hypokalaemia which all are mild and transient. Conclusion: In young children with acute watery diarrhea, racecadotril is an effective and safe treatment along with rehydration therapy. DS (Child) H J 2020; 36(1) : 8-13